Exploring Sources of Information and Religious Beliefs in Regard to HPV and Vaccination Among Hispanic/Latino College Students in the USA - Tung, Wei-Chen (Journal of religion and health, 2023)
We identified (a) sources of and communication about HPV information and (b) factors (e.g., religious affiliations) related to information sources and communication regarding HPV among Hispanic/Latino college students attending US institutions. Applying a cross-sectional design, we recruited 209 participants from US colleges. Most participants used healthcare professionals for their sources and communication about HPV-related information. Respondents who were practicing Catholics tended to use the Internet and healthcare professionals as their sources for HPV-related information. Healthcare professionals, TV, schoolteachers, same-sex friends, and family members affected participants’ HPV vaccination, knowledge, and attitudes. Religious faith may influence information-seeking behaviors and requires more research.